Evidence of Q Fever and Rickettsial Disease in Chile - Tapia, Teresa (Trop Med Infect Dis, 2020)
Q fever and rickettsial diseases occur throughout the world and appear to be emergent zoonoses in Chile. The diagnosis of these diseases is currently uncommon in Chile, as their clinical presentations are non-specific and appropriate diagnostic laboratory assays are of limited availability. During a recent outbreak of undiagnosed human atypical pneumonia, we serologically investigated a series of 357 cases from three regions of southern Chile. The aim was to identify those caused by Coxiella burnetii and/or Rickettsia spp. Serological analysis was performed by ELISA and an immunofluorescence assay (IFA) for acute and convalescence sera of patients. Our results, including data from two international reference laboratories, demonstrate that 71 (20%) of the cases were Q fever, and 44 (15%) were a likely rickettsial infection, although the rickettsial species could not be confirmed by serology. This study is the first report of endemic Q fever and rickettsial disease affecting humans in Chile.